Energetics of Excitatory and Inhibitory Neurotransmission in Aluminum Chloride Model of Alzheimer’s Disease: Reversal of Behavioral and Metabolic Deficits by Rasa Sindoor - Saba, Kamal; Rajnala, Niharika; Veeraiah, Pandichelvam; Tiwari, Vivek; Rana, Rohit K.; Lakhotia, Subhash C.; Patel, Anant B. (Frontiers in Molecular Neuroscience, 2017)
Alzheimer’s disease (AD) is an age-related neurodegenerative disorder, characterized by progressive loss of cognitive functions and memory. Excessive intake of aluminum chloride in drinking water is associated with amyloid plaques and neurofibrillary tangles in the brain, which are the hallmark of AD. We have evaluated brain energy metabolism in aluminum chloride (AlCl3) mouse model of AD. In addition, effectiveness of Rasa Sindoor (RS), a formulation used in Indian Ayurvedic medicine, for alleviation of symptoms of AD was evaluated. Mice were administered AlCl3 (40 mg/kg) intraperitoneally once a day for 60 days. The memory of mice was measured using Morris Water Maze test. The 13C labeling of brain amino acids was measured ex vivo in tissue extracts using 1H-[13C]-NMR spectroscopy with timed infusion of [1,6-13C2]glucose. The 13C turnover of brain amino acids was analyzed using a three-compartment metabolic model to derive the neurotransmitter cycling and TCA cycle rates associated with glutamatergic and GABAergic pathways. Exposure of AlCl3 led to reduction in memory of mice. The glutamatergic and GABAergic neurotransmitter cycling and glucose oxidation were found to be reduced in the cerebral cortex, hippocampus, and striatum following chronic AlCl3 treatment. The perturbation in metabolic rates was highest in the cerebral cortex. However, reduction in metabolic fluxes was higher in hippocampus and striatum following one month post AlCl3 treatment. Most interestingly, oral administration of RS (2 g/kg) restored memory as well as the energetics of neurotransmission in mice exposed to AlCl3. These data suggest therapeutic potential of RS to manage cognitive functions and memory in preclinical AD.